Effects of R&D investments and market signals on international acquisitions: Evidence from IPO firms - Cheng-Wei Wu; Jeffrey J. Reuer (Journal of Risk and Financial Management, 2021)
We investigate how intangible assets in the form of R&D influence firms' hazards of engaging in international acquisitions. On the one hand, previous research has noted that the tacit and redeployable nature of R&D investments may prompt firms to expand their operations overseas and create value from international acquisitions. On the other hand, it is difficult for other firms to evaluate the quality and prospects of an acquirer's intangible resources, thereby hampering its ability to finance and execute international M&A deals. In the context of international acquisitions undertaken by firms just completing their initial public offerings (IPOs), we argue and find that the IPO firm's engagement in post-IPO international acquisition activity is generally negatively related to its R&D intensity. This effect contrasts previous arguments on the internalization advantages possessed by R&D-intensive firms. We also argue that firms able to convey their resources and prospects through such signals as previous international alliances and foreign sales can mitigate information problems presented by their intangibles, and thus carry out and benefit from cross-border acquisitions. We therefore identify an unexamined tradeoff that R&D investments present in the international M&A context and discuss how international signals can facilitate cross-border transactions subject to various market frictions.
Keywords: 330; international acquisitions; R&D intensity; signaling theory